Presentation and Immediate Outcome of Surgical Treatment of Patients with Carcinoma of the Stomach - A Comparative Study between Young and Elderly patients (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Carcinoma of the stomach is a common malignancy and have a high mortality. Incidence under the age of 45 is comparatively low but appear more aggressive then elderly group. This study was designed to describe the presentation and operative findings in the two groups of patients and to record the outcome of surgical management in these patients.A total of 86 cases were included in this study. 14 were from below 40 years (young group) and 72 were above 40 years (elderly group). Young patients had less definitive symptoms than elderly group. Pain (85.71%) and vomiting (78%) were the most prominent symptoms in both the groups. But in elderly a significant number 54(75%) of cases had anorexia. Lump and visible peristalsis were present in both groups in approximately similar proportion. Histopathologically younger patients had more aggressive disease than the elderly group.The operability in carcinoma of the stomach was more in young group probably due to physical fitness of patient. In both the groups antrum was the commonest site of malignancy. The incidence of malignancy in body was more in young patients. In young group tumor status was T4 in 54.5% and in elderly group 56% was in T4 stage. 80% had lymph node involvement in both the groups. Resection was possible in young group in about 90% and gastrojejunostomy in 9.09% cases. Conversely, in the elderly group resection was possible in 58% and gastrojejunostomy was done in 42% cases. Total gastrectomy was done in 18.18% in young group and 4% in elderly group. Another important finding was partial gastrectomy was done in 72.73% in young but 46% in elderly only. The mortality was more (18.2%) in young group in comparison to (10%) in elderly.Gastric carcinoma was found more aggressive in young with high mortality and morbidity. Efforts should be taken for early diagnosis and prompt surgical treatment. DOI: 10.3329/jbcps.v28i3.6507J Bangladesh Coll Phys Surg 2010; 28: 145-150